MoM Analysis of Apertures in Chiral Bodies of Revolution - Qutubuddin, Khaja; Mustacoglu, Halid; Mautz, Joseph R.; Arvas, Ercument (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A chiral body of revolution (BOR) which is partially covered by a thin conducting shield is analyzed using the Method of Moments (MOM). The axisymmetric system is excited by a plane wave. The internal fields and the far scattered fields are computed. The problem is solved using the surface equivalence principle. The scattered fields outside the structure are assumed to be produced by an equivalent magnetic surface current that exists on the unshielded part of BOR surface and an external equivalent electric surface current that exists over the entire BOR surface. These two currents are assumed to radiate in the unbounded external medium. Similarly, the internal fields are assumed to be produced by the negative of the above magnetic current and an internal electric surface current that exists over the entire BOR surface, but is an independent unknown only on the shielded part of the BOR surface. These two currents radiate in the unbounded internal medium. Enforcing the boundary conditions at the surface of the BOR results in a set of coupled integral equations for the three equivalent surface currents. These equations are solved numerically using the MOM. The computed results for the partially shielded spherical chiral body are in excellent agreement with other data.